The New Asian power dynamic - Maharajakrisha Rasgotra (New Delhi : Sage Publications, 2007)
307 page
Keywords: Asia -- Foreign relations; Asia -- Foreign relations -- United States..; Power (Social sciences) -- Asia; United States -- Foreign relations -- Asia